Proceedings of the 2nd  International Seminar on Guidance and Counseling 2019 (ISGC 2019) 2020
DOI: 10.2991/assehr.k.200814.064
|View full text |Cite
|
Sign up to set email alerts
|

The Success Story From Inclusive School: A Case Study

Abstract: This paper provided a descriptive explanation about a self-confidence of slow learner student (SLS). Self-confidence is an indicator to measure the successfulness of student with a special need. As the goal of inclusive school that provided an environment to makes all children learning together. The case study method is used to find factors that influence the selfconfidence of SLS. The result of the study found there are 3 factors that a teacher should do to improve the self-confidence of SLS. First is trust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They accentuate their self-improvement as a woman along with their given role (Budiati, 2010). The research found mother's resilience is a significant factor in encouraging children's self-confidence (Dewanti & Novitasari, 2020). In that sense, how they manage their anxiety is influenced by their values as Javanese women.…”
Section: Discussionmentioning
confidence: 94%
“…They accentuate their self-improvement as a woman along with their given role (Budiati, 2010). The research found mother's resilience is a significant factor in encouraging children's self-confidence (Dewanti & Novitasari, 2020). In that sense, how they manage their anxiety is influenced by their values as Javanese women.…”
Section: Discussionmentioning
confidence: 94%